A star is born (2018) [videorecording (DVD)] - Cooper, Bradley; Cooper, Bradley; Cooper, Bradley; Cooper, Bradley; Lady Gaga; Elliott, Sam, 1944-; Clay, Andrew Dice (Warner Bros. Entertainment, 2019)
A musician helps a rising singer find fame as his own career begins a downward spiral.